Chains of tragedy: The impact of bullying victimization on mental health through mediating role of aggressive behavior and perceived social support - Guo, Yi; Tan, Xiao; Zhu, Qiu-jin (Frontiers in Psychology, 2022)
Objective: To demonstrate the chain of mediating effects of bullying victim’s aggressive behavior and perceived social support in the relationship between bullying victimization and mental health among adolescents. Methods: A total of 3635 adolescents responded to questions on bullying victimization, aggressive behavior, perceived social support, and mental health measurements including anxiety, depression, and subjective well-being scale combined. Results: (1) Bullying victimization was significantly correlated with aggressive behavior, perceived social support, and mental health, including anxiety, depression and subjective well-being. (2) Bullying victimization not only negatively predicts mental health levels but also has an indirect impact on mental health through three pathways: a separate mediating effect on aggressive behavior, a separate mediating effect on perceived social support, and a chain mediating effect on both. Conclusion: The present results demonstrate bullying victims who conduct maladaptive behavior that would lead to the change in their perceived social support and mental health problems. Violence begets violence and provides no constructive solutions, instead, produces a tragic chain of victimization. Further implications are discussed accordingly.